Intrapartum Amniotic Fluid Index as Predictor of Perinatal Outcome in High Risk Pregnancy - Apichart Chittacharoen (2022)
Objective: To determine the diagnostic value of amniotic fluid index in the early intrapartum period for predicting of perinatal outcome in high risk pregnancy. Methods: Four hundred and fifty high risk pregnant women of at least 34 weeks gestation were recruited at Department of Obstetrics and Gynaecology, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand. The measurement of four-quadrant amniotic fluid index was performed by ultrasonography in the early intrapartum period. The amniotic fluid index £ 5 cm was the cutoff point for the predicting of poor perinatal outcome. The result of amniotic fluid index was compared to the perinatal outcome using sensitivity, specificity, negative predictive value, positive predictive value and accuracy. Results: Among 450 high risk pregnancies, 92 cases (20.44%) were amniotic fluid index £ 5 cm, and 358 cases (79.56%) were amniotic fluid index > 5 cm. The incidence of poor perinatal outcome was 16.67%. An intrapartum amniotic fluid index of ≤ 5 cm, in comparison with > 5 cm, is associated with an increased risk of poor perinatal outcome (P < 0.05). The sensitivity, specificity, positive and negative predictive values and accuracy of four-quadrant amniotic fluid index ≤ 5 cm for predicting perinatal outcome were 72%, 89.86%, 58.69%, 94.13%, and 86.88%, respectively. Conclusion: An intrapartum amniotic fluid index of ≤ 5 cm is associated with a significantly increased risk of poor perinatal outcome. The amniotic fluid index measurement is an effective diagnostic test to identify fetus at risk in the intrapartum period of the high risk pregnancy.